ANALISIS PENERAPAN ISM CODE GUNA MENUNJANG KESELAMATAN KERJA DI MV. MABAH - Cyprianus Bala Lembang; Makmur; Furnayanti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The implementation of the International Safety Management (ISM) Code plays an important role in ensuring occupational safety on board ships. However, workplace accidents may still occur due to gaps in the implementation of safety procedures. This study aims to examine the implementation of the ISM Code in relation to occupational safety on board MV. Mabah, a cargo reefer vessel transporting frozen fishery cargo. The study employed a qualitative approach using interviews, observations, and documentation, with data analyzed descriptively. The results indicate that although MV. Mabah has formally complied with the ISM Code through a valid Safety Management Certificate and documented safety procedures, its implementation has not been fully effective. Several shortcomings were identified, including inconsistent compliance with safety procedures, limited specialized training, inadequate use of Personal Protective Equipment (PPE), insufficient operational supervision, and a weak safety reporting culture. These conditions reduce the effectiveness of the safety management system and increase the risk of workplace accidents. Therefore, strengthening safety training, improving supervision, enhancing communication among crew members, and fostering a stronger safety culture are recommended to improve the implementation of the ISM Code and occupational safety on board MV. Mabah.